SYNERGISTIC DRUG COMPATIBILITY OF SUMATRIPTAN SUCCINATE AND METOCLOPRAMIDE HYDROCHLORIDE (IN SITU GEL FORMULATIONS) FOR NASAL DRUG RELEASE OPTIMIZATION - RIYA V KALEBAR; PANKAJ GAJARE; MAMLE DESAI SN; VISHAL U KALEBAR; RAVINDRANATH H ALADAKATTI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Migraine is a prevalent neurological condition that causes lifelong tenacious headaches and significantly impacts the daily lives of individuals. Despite being frequently underestimated or neglected, it affects the individual’s routine activities, performance, self-confidence, and identity. Treatment often involves the administration of painkillers, which can lead to various complications. This study aimed to develop and characterize an in situ nasal formulation of sumatriptan succinate and metoclopramide hydrochloride to enhance drug residence time in the nasal cavity and improve drug bioavailability. Methods: Eight formulations of intranasal in situ gels were prepared using the “Cold Method” and evaluated for various parameters, including appearance, texture, viscosity, pH, gel strength, gelation temperature, drug content, and in vitro/ex vivo drug diffusion. FT-IR studies confirmed no interactions between sumatriptan succinate, metoclopramide hydrochloride, and the excipients. Simultaneous estimation method was used to evaluate drug content, in vitro and ex vivo drug diffusion. Results: Among the formulations, “Sumatriptan Succinate Metoclopramide Hydrochloride Polymer (SMP8)” exhibited the most favorable characteristics. The percent cumulative drug release was determined to be 96.803±0.0015 for sumatriptan succinate and 92.569±0.0028 for metoclopramide hydrochloride, aligning with the Higuchi model kinetics. In vitro and ex vivo diffusion studies demonstrated that SMP8 provided sustained drug release for up to 9 h, making it the optimal dosage formulation for nasal drug delivery in the treatment of migraine. Conclusion: This study’s findings suggest that the developed intranasal in situ gel formulation, SMP8, effectively releases sumatriptan succinate and metoclopramide hydrochloride over an extended period. By improving drug residence time and bioavailability, this formulation has the potential to enhance the therapeutic efficacy and patient compliance in the management of migraine.